Characterisation of Kaposi's sarcoma-associated herpesvirus (KSHV)-driven pathology and disease outcome in HIV infected South African patients - Blumenthal, Melissa (Department of Integrative Biomedical Sciences (IBMS), 2020)
Kaposi's sarcoma-associated herpesvirus (KSHV), a gamma-herpesvirus with a particularly high seroprevalence in Sub-Saharan Africa (SSA), is the etiological agent of the endothelial tumour Kaposi's sarcoma (KS), the most common acquired immunodeficiency syndrome (AIDS)-related malignancy worldwide and particularly in SSA. It also causes primary effusion lymphoma (PEL), multicentric Castleman disease (MCD) and KSHV inflammatory cytokine syndrome (KICS). AIDS-related deaths have declined, due to global scale-up of antiretroviral therapy (ART). However, the vast majority of these occurred in SSA, where tuberculosis (TB) is the leading cause of mortality among human immunodeficiency virus (HIV)-infected individuals, accounting for a third of all AIDS-related deaths. The exceptionally high burden of suspected TB in SSA causes misdiagnosis or delayed diagnosis of diseases mimicking TB, such as several pathologies associated with KSHV. KSHV infection is essential but insufficient for the development of KS and other KSHV-associated pathologies; precipitating factors, such as HIV-related immune suppression and potentially genetic predisposition, are required. The erythropoietin-producing hepatocellular carcinoma (Eph) receptor A2 protein (EPHA2) tyrosine kinase receptor is a promising candidate for studies on genetic variants as it potentially acts on two levels: susceptibility to KSHV infection (being one of the key receptors utilised by KSHV for cell entry and intracellular trafficking) and susceptibility to KS development (being implicated in oncogenesis). Despite the high seroprevalence in SSA, the contribution of dysregulated KSHV lytic replication or host KSHV receptor variations to disease outcome in HIV-infected patients is unknown. We hypothesised that KSHV lytic reactivation plays yet unrecognised roles for morbidity and mortality in high HIV settings and to this end, we conducted a cohort study of 682 HIV-positive critically ill patients admitted to Khayelitsha Day Hospital, South Africa, investigated for TB, and followed for 12-weeks to ascertain vital status. We demonstrated that elevated blood KSHV viral load (VL) was a strong predictor of death in hospitalised HIV-infected patients without microbiologically proven TB. Further, we identified and validated variants in the EPHA2 protein tyrosine kinase and sterile alpha motif domains that were significantly associated with susceptibility to infection, KS development and/or KSHV VL in 300 South African HIV-infected patients, by aggregate by-gene analysis. In order to elucidate the functional significance of the identified EPHA2 missense mutations, we knocked out endogenous EPHA2 by CRISPR/Cas9 in the human endothelial cell line, HuARLT2, and reintroduced the wild type and mutant EPHA2 open reading frames by lentiviral transduction. These engineered cells were assessed for baseline EPHA2 phosphorylation levels and susceptibility to KSHV infection utilising recombinant KSHV in binding, internalisation and infection assays. We found that the EPHA2 mutant c.2254T>C (p.Leu700Pro) in the tyrosine kinase domain, associated with KS in our patient cohort, was deficient in tyrosine phosphorylation and less permissive to rKSHV infection when introduced as a single mutation or as a double mutant together with c.2257A>C (p.Asp701Ala) which was found to be in linkage disequilibrium with it. Another tyrosine kinase domain variant, c.2688G>S (p.Ala845Pro), found to be overrepresented among KS patients, had enhanced baseline tyrosine phosphorylation levels. These findings validated the patient-derived data on the molecular level by assigning functional consequences to some mutants which might have implications for the development of future biomarkers predicting KS susceptibility in high-risk populations. In summary, this novel research contributes to the understanding of KSHV-associated pathology and disease outcome. It identified KSHV VL as a potential biomarker to predict KSHV-associated diseases and mortality and assessed the contribution of KSHV entry receptor EPHA2 variations to KSHV-associated pathologies, with potential clinical implications, by facilitating the development of novel diagnostic and surveillance tools.